Television Amongst Friends: Medium, Art, Media. Issue 3 (1st January 2014) - Cardwell, Sarah
Abstract: From the perspective of analytic philosophical aesthetics, this paper disputes the commonplace practice of referring to television as a 'medium'. It proposes instead that television be regarded as an art composed of many media. Individual works employ various media available to television and also to other arts. The paper evaluates the usefulness of these distinctions for our conceptual understanding of television, appraisal of television works and appreciation of television in relation to other arts. Via its reconfiguration of 'medium/media', it challenges narrowly contemporary notions of the televisual, positing a more historicised model and situating television alongside other arts - amongst friends.